Dal Caucaso al Mar d'Azov L'impatto dell'invasione mongola in Caucasia fra nomadismo e società sedentaria (1204-1295). Nuova edizione riveduta e aggiornata - Pubblici, Lorenzo (Biblioteca di storia, 2018)
This essay is republished ten years later because, on the one hand, the current geopolitical situation has radically changed compared to then. The Caucasus represents a decisive political and social link between Western societies and Asia, as well as the historical link between Christianity and Islam, today even more than ten years ago. On the other hand, over the last two decades, particularly in the last ten years, scholars have been paying increasingly more attention to the history of the Mongols. Research and publications have multiplied in Europe, the United States, Russia and all those countries having direct or indirect relationships with the empire created by Genghis Khan. Many works published in past years had been confined to the local dimension, because they were written in hard-to-access languages, from Hungarian to Persian, from Russian to Chinese. However, since the beginning of the 2010s, there have been intense translation works of the sources into English, as well as a significant research activity, whose results are often being published in English, therefore becoming accessible to the international scientific community.